Training on Digital Module Creation to Enhance Teacher Competency - Prima Nucifera; Syardiansah Syardiansah; Muhammad Yakob (Universitas Lambung Mangkurat, 2024)
Digitalization aims to make work easier and optimize time and resources as efficiently as possible. Teachers, like it or not, must face digitalization in this era of society 5.0. The benefits of digitizing education are that it makes teacher and student schedules more flexible, speeds up and simplifies the evaluation process, and creates a more personalized learning experience. The problem partners face is the lack of teachers' experience and knowledge in creating digital modules. Teachers are required to apply digitalization in learning based on the current implementation of the Independent Curriculum. Partner schools lack funds to support training activities to improve teacher competency. There are no instructors who are able to provide training in creating digital modules. The aim of this service activity is to provide education in the form of training and assistance in creating digital modules for MTsN Seuruway teachers, as an effort to increase competency. The method used is Participatory Action Research by involving all participants in training activities. All the teachers at the MTsN Seuruway school were involved in this activity. The results achieved after this activity were that the teachers could use the applications taught in the training. Teachers are able to create digital modules with the Canva program. Increased teacher understanding in updating the teaching modules given to students. The conclusion that can be drawn is that this training has provided additional knowledge and new skills so that teachers can create teaching media that are more interactive and interesting for teaching students.